An Efficient FeCl3-Catalyzed Condensation of Thiols with 1,3-Dicarbonyl Compounds under Solvent-Free Conditions - Kumari, Kumkum; Singh, Krishna Nand (Synlett, 2014)
A practical and environmentally friendly method has been developed for the synthesis of thiol-substituted cyclohex-2-enones using a FeCl3-catalyzed condensation of cyclic 1,3-dicarbonyl compounds and aromatic/aliphatic thiols under solvent-free conditions at ambient temperature.
Keywords: condensation; thiols; green chemistry; Lewis acids; iron